Samoan Philosophy of Nursing: A basis for culturally proficient care and policy - I. S. Enoka (2018)
Aim: To explore nurses' perspectives about the Samoan Philosophy of Nursing, and determine its feasibility for nursing care of Samoans internationally. Background: This philosophy is the conceptual cultural framework for nursing law, practice, education and research in Samoa, and was developed by Samoan nurses who recognized the need for guidance to deliver quality, culturally competent and proficient health care. Design: A mixed method study, employing a questionnaire and ethnographic methods. Method: The Samoan Philosophy of Nursing Questionnaire sought demographic data and aspects about the philosophy from 95 registered nurse clinicians, administrators and educators throughout Samoa during 2012. Descriptive statistics were used for data analysis. Additionally, 19 focus groups (5-6 participants each) and 19 in-depth interviews were held to further explore these aspects, as well as participant observations. Descriptive statistics were used to analyse quantitative data, and Spradley's ethnographic method was adopted for analysing the qualitative data. Findings: Of 95 questionnaires analysed, 70% of participants reported using the philosophy all the time, and 30% most of the time. They placed a high satisfaction rate, value and importance on this philosophy. From the ethnography, six major themes emerged: valuable framework of learning; conceptual framework for holistic assessment; benchmark for regulating and monitoring practice improving interaction and culturally proficient practice; potential use for Samoans overseas; and maintaining quality health and the dignity of people. Conclusion: This first-time study evaluated the Samoan Philosophy of Nursing and adds to nursing knowledge. Findings confirmed its usefulness as a culturally based conceptual framework to facilitate, regulate and monitor education, research and practice for sustainable health outcomes in Samoa, and for Samoans living abroad. Implications for nursing policy and education: It is important that Samoans living abroad receive culturally proficient care, but this requires the support of policymakers, nurse leaders and educators so that nurses internationally can access and competently utilize relevant aspects of this philosophy in practice. © 2014 International Council of Nurses.